Exploring The Factors Of Employee Retention In Bangladesh Private Universities / Shamsel Arifin and Rafiduraida Abdul Rahman - Arifin, Shamsel; Abdul Rahman, Rafiduraida (Universiti Teknologi MARA, Kedah, 2019)
The main objective of this study is to explore the factors affecting employee retention in Bangladesh Private Universities. This study adopted a qualitative method using semi-structured interview. 10 lecturers from three different private universities in Bangladesh were selected as the sample for this research. Data was analysed through the coding method and member checking technique was used to check the validity and reliability of the data. Result clearly showed that employee retention was influenced by the compensation most, followed by work life balance, employee empowerment and training and development facilities. The study also found that factors such as transportation facilities and preferable subject also affect employee retention. As this study explores the factors of employee retention, management of the private universities will be benefited to develop their retention strategies by considering the significant factors. Furthermore, this study will add more research value on employee retention in Bangladesh higher educational organization which is currently limited.